MEDB-53. Incidence of Hearing impairment in childhood Medulloblastoma Survivors treated in King Fahad Medical City KFMC Saudi Arabia. (3rd June 2022) - Mahmodi, Mohammed Al; Mobark, Nahla Ali; Almowanes, Demah A; AlGhunaim, Haya N; Kattan, Nad E; Aljabarat, Wael abdel Rahman; Alotabi, Fahad; Rayis, Mohammed; AlNaqib, Zaid G; Balbaid, Ali Abdullah O; Alharbi, Musa
Abstract: Medulloblastoma MB is the most common childhood CNS tumor treated with intensive multimodalities therapy Surgery, Radiation and Cisplatin chemotherapy which causing significant Hearing impairment (HI) with profound impact on child's quality of life. METHOD : Retrospective study evaluating risk factors & (HI) incidence in childhood MB survivors treated in KFMC between 2010 and 2020. (HI) was graded using the National Cancer Institute (NCI) Grades (1-4) ALL patients received 6 weeks of Risk adapted CSI radiotherapy concurrent with daily oral Etoposide. patients were treated with 2 different Maintenance chemotherapy German HIT-MED MB protocol 8 Maintenance cycles (Cisplatin 70 mg/m² x 1d /lomustine/VCR) Cumulative dose of Cisplatin 560 mg/m2 KFMC MB SAPHOS protocol 6 Maintenance cycle alternating A&B. cycle A: Cisplatin 90 mg/m² x 1d & 3 weeks of daily oral Etoposide. cycle B: Cyclophosphamide x 2 d & Vincristine Cumulative dose of Cisplatin 270 mg/m2. RESULTS: At Median follow-up of 5 years total of 78 MB survivors, male predominance 66.7% Median age at diagnosis 82 months post end of therapy 28.2% maintain normal hearing while 71.8% had hearing decline compared with baseline audiology Median time of onset of hearing decline was 7 months after start of radiation therapy Significant (HI) (NCI grade 3/4) in 26.9% of patients, and 23.1% required hearing aid use NO statistically difference in incidence of significant (HI) in patients treated with HIT-MED protocol (26.7%) & patients treated with KFMC MB-SAPHOS protocol (27.1%) OR those treated as Average-Risk CSI radiotherapy 22.9% Vs High-Risk CSI radiotherapy (30.2%), patients age at diagnosis (< or > 5 years) does not affects HI incidence. CONCLUSIONS: significant hearing impairment incidence was not affected by Radiation doses OR cumulative Cisplatin dose. Our study will form base line for future studies to modify therapy related Toxicity and improve outcome of childhood MB in Saudi Arabia.